2016
DOI: 10.7554/elife.20770
|View full text |Cite
|
Sign up to set email alerts
|

Thalamo-cortical axons regulate the radial dispersion of neocortical GABAergic interneurons

Abstract: Neocortical GABAergic interneuron migration and thalamo-cortical axon (TCA) pathfinding follow similar trajectories and timing, suggesting they may be interdependent. The mechanisms that regulate the radial dispersion of neocortical interneurons are incompletely understood. Here we report that disruption of TCA innervation, or TCA-derived glutamate, affected the laminar distribution of GABAergic interneurons in mouse neocortex, resulting in abnormal accumulation in deep layers of interneurons that failed to sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 75 publications
5
22
0
Order By: Relevance
“…there was an increase in the density of LHX6-positive cells in layer 6 and below, and a decrease in the middle layers ( Fig.6F), while the total density was not significantly different between the two genotypes ( Fig.6G). These results on the neonatal PFC are remarkably similar to a recent report on sensory and motor cortex of thalamus-specific Gbx2 mutant mice (Zechel et al, 2016). Thus, there is an early, cortex-wide role of thalamocortical projections in controlling the radial distribution of MGE-derived interneurons.…”
Section: Lack Of Thalamus-pfc Connectivity Results In Early Aberrancysupporting
confidence: 90%
See 4 more Smart Citations
“…there was an increase in the density of LHX6-positive cells in layer 6 and below, and a decrease in the middle layers ( Fig.6F), while the total density was not significantly different between the two genotypes ( Fig.6G). These results on the neonatal PFC are remarkably similar to a recent report on sensory and motor cortex of thalamus-specific Gbx2 mutant mice (Zechel et al, 2016). Thus, there is an early, cortex-wide role of thalamocortical projections in controlling the radial distribution of MGE-derived interneurons.…”
Section: Lack Of Thalamus-pfc Connectivity Results In Early Aberrancysupporting
confidence: 90%
“…The current study also revealed an early role of the thalamus in regulating the radial positioning of MGE-derived interneurons in neonatal PFC. The altered positioning of interneurons was highly reminiscent of what was found in sensory and motor areas 12 .…”
Section: Universal and Area-specific Roles Of The Thalamus In Neocortmentioning
confidence: 70%
See 3 more Smart Citations